(untitled) (Ustozlar uchun, 2025)
The rise of electric cars represents a significant shift in the automotive industry, driven by technological advancements, environmental concerns, and changing consumer preferences. This paper examines the impact of electric vehicles (EVs) on the environment, focusing on their potential to reduce greenhouse gas emissions, improve air quality, and decrease dependence on fossil fuels. It also addresses challenges such as battery production, charging infrastructure, and the source of electricity used to power EVs. By analyzing current trends and future projections, this study aims to provide a comprehensive understanding of the environmental implications of the growing adoption of electric cars.